Segmentasi Citra Digital Dengan Menggunakan Algoritma Khutlang - Nur Aisyah Panjaitan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The segmentation process in digital images is done with edge detection to provide a target path along the edge (edge) of the image object. The edge in the image is the area on the edge of the image object with strong contrast intensity, so that the intensity jumps from one pixel to another. Edge detects images by significantly reducing the amount of data and filtering out useless filtering, and also preserving the important properties needed in the image in this case which supports the appearance of the edges of the image. Edge Detection in an image of a process that results in the edges of image objects, the purpose is to mark the details of the image and to improve the details of the blurred image, which occurs due to errors or the effects of the acquisition process image. There are many methods for detecting this edge, but the method for locating this edge is characteristic of the